Prophage encoding toxin/antitoxin system PfiT/PfiA inhibits Pf4 production in Pseudomonas aeruginosa. Issue 4 (4th April 2020) - Li, Yangmei; Liu, Xiaoxiao; Tang, Kaihao; Wang, Weiquan; Guo, Yunxue; Wang, Xiaoxue
Summary: Pf prophages are ssDNA filamentous prophages that are prevalent among various Pseudomonas aeruginosa strains. The genomes of Pf prophages contain not only core genes encoding functions involved in phage replication, structure and assembly but also accessory genes. By studying the accessory genes in the Pf4 prophage in P. aeruginosa PAO1, we provided experimental evidence to demonstrate that PA0729 and the upstream ORF Rorf0727 near the right attachment site of Pf4 form a type II toxin/antitoxin (TA) pair. Importantly, we found that the deletion of the toxin gene PA0729 greatly increased Pf4 phage production. We thus suggest the toxin PA0729 be named PfiT for Pf 4 i nhibition t oxin and Rorf0727 be named PfiA for Pf iT a ntitoxin. The PfiT toxin directly binds to PfiA and functions as a corepressor of PfiA for the TA operon. The PfiAT complex exhibited autoregulation by binding to a palindrome (5′‐AATTC N5 GTTAA ‐3′) overlapping the ‐35 region of the TA operon. The deletion of pfiT disrupted TA autoregulation and activated pfiA expression. Additionally, the deletion of pfiT also activated the expression of the replication initiation factor gene PA0727. Moreover, the Pf4 phage released from the pfiT deletion mutant overcame the immunity provided by the phage repressor Pf4r. Therefore, this study reveals that the TA systems in Pf prophages can regulate phage production and phage immunity, providing new insights into the function of TAs in mobile genetic elements. Abstract : PfiT/PfiA in Pf4 prophage forms a type II toxin‐antitoxin system in Pseudomonas aeruginosa . PfiT inhibits production of Pf4 phage.